Pengaruh pengeluaran Pemerintah Bidang Infrastruktur Fisik dan Sosial Terhadap Pertumbuhan Ekonomi kalimantan Barat tahun 2008-2012 - B01110099, Wirdaniati (Jurnal Pembangunan dan Pemerataan, 2015)
This study entitled "The Effect of Government Spending Physical and Social Infrastructure Against West Kalimantan Economic Growth Year 2008-2012", which aims to test and analyze "Government Spending Influence of Physical and Social Infrastructure Against West Kalimantan Economic Growth in 2008-2012". The analysis used a panel regression analysis of the data was used to examine the relationship between government expenditure variable fields of physical and social infrastructure to economic growth of the district / city in the province of West Kalimantan. The data used are secondary data years 2008-2012 which consists of 12 districts / cities in West Kalimantan Province from the Central Statistics Agency (CSA) and the Ministry of Finance. C The results of the calculation and analysis of data, it can be explained that the physical infrastructure of government spending and a no significant positive effect on economic growth obtained t value of (0.2492 >0.05), government spending social infrastructure and significant positif effect on economic growth (-0.00001 < 0.05). The test results simultaneously obtained value of F statistic of 5.239952 to the value of prob (Fstatistik) of 0.000013 is smaller than 0.05 (probability< 0.05). This means that the economic growth is affected jointly by government spending physical and social infrastructure. Keywords: government spending areas of physical, social, economic growth.